Correlation between estrus onset and ovarian parameters in dairy goats - Cortat, Paula Renata; Dias, Mirela Balistrieri; Paula, Cleber Jonas Carvalho de; Rangel, Paulo Sergio Cerqueira; Oliveira, Maria Emilia Franco [UNESP]; Souza-Fabjan, Joanna Maria Gonçalves de; Fonseca, Jeferson Ferreira da (Universidade Federal de Goiás, 2022)
This study assessed the effects of social dominance on the behavioral estrus and ovarian parameters of dairy goats subjected to synchronous estrus induction during the non-breeding season. Synchronous estrus was induced in 23 dairy goats allocated to collective pens. Ovarian ultrasonography was performed at 12 h intervals from device removal to ovulation. Upon estrus onset (EO) detection, the goats were immediately removed from the pens. Dominance was scored according to EO in relation to device removal in each pen, with HD - high dominants (<36 h; n = 8), MD - medium dominants (36 to 48 h; n = 10) and LD - low dominants (>48 h; n = 5). Goats in estrus underwent flexible time artificial insemination (FxTAI) according to EO. The estrus response was 100.0%. The interval to estrus was longer (P<0.05) in LD (53.7 ± 6.5 h) than in MD (37.9 ± 5.5 h) and HD goats (32.3 ± 6.6 h), while the interval from device removal to ovulation was similar (P>0.05) among all groups. The interval from EO to FxTAI was longer in HD goats compared to the other groups (P<0.05). In conclusion, although social hierarchy influenced the time of EO, the ovarian parameters, including ovulation, were not affected.
Keywords: goats; estrus behavior; follicular dynamics; social hierarchy; ovulation